AN EXPERIMENT TO ANALYZE THE IMPACT OF STEAM ON THE PRODUCTIVITY OF THE STALAM RF 85 KW YARN DRYER - HEMANTH KUMAR JAWAHAR (Journal of Engineering Studies and Research)
Radio Frequency is one of the most commonly used technologies in the processing industries like textile, rubber, paper and many other sectors for drying purposes. The RF STALAM 85kW is a machine used to dry the yarn obtained after the dyeing and hydro extraction process. This machine uses radio frequency to remove the moisture content from the dyed yarn. In this research paper, I would like to share the findings of an experiment conducted on the RF STALAM 85kW yarn dryer machine. In this experiment, I have three trials each with and without the steam at variable conveyor belt speeds. The trials have been conducted at conveyor belt speeds of 5m/hr,5.5m/hr and 6m/hr in the presence and absence of steam. The primary objective of the research is to improve the productivity of the STALAM RF machine. The secondary objective of the research is to find out the impact of steam on the yarn drying ability of the machine. The tertiary objective of the research is to find the optimum speed. At the end of the experiment, I calculated the per day production to conclude the optimum speed to run the STALAM RF 85kW yarn drier machine to obtain maximum production with and without steam. From the above research, I have concluded that the conveyor belt speed and steam increase the productivity of the machine.